A need analysis for evaluation media development of the project-based quiz creator in computer and basic network subject - Saputra, Deni; Sukardi, Sukardi; Giatman, M; Edidas, Edidas (Universitas Negeri Padang, 2020)
This need analysis research consists of observations and literature studies. This research aims to 1) describe student learning outcomes in the learning process. 2) find the problems faced by students in Computer and Basic Network subject. 3) find Evaluation media solutions needed in conducting the assessment. This research was a descriptive quantitative research. The subjects of this research were 31 students of Grade X TKJ in Vocational High School 2 Lubuk Basung. The data were obtained from questionnaires and analysis through the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) to get conclusions. The results of the research showed that: 1) there were still many students who had not yet reached the Minimum Learning Standard. 2) the learning media used did not make it easy for students to understand the material. 3) the evaluation media used took a long time to get results.